PEMBERDAYAAN UMKM MAKANAN MELALUI DIVERSIFIKASI PRODUK, SERTIFIKASI, DAN STRATEGI PEMASARAN BERKELANJUTAN BAGI ANGGOTA GOW KOTA SEMARANG - Janti Soegiastuti ,; Nurchayati, Nurchayati; Suparmi, Suparmi; Lisa Erfi Yunita , (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program was initiated due to the limited capacity of food MSMEs under the Gabungan Organisasi Wanita (GOW) in Semarang City, particularly in product diversification, certification, and sustainable marketing. The goal is to enhance competitiveness through an integrated mentoring approach in these three areas. The program applied the Participatory Action Research (PAR) method in five stages, including training, mentoring, and product showcasing. The results show significant improvement: 86% of MSMEs developed new product variants, 100% obtained PIRT certification, and 96% established active digital marketing platforms. On average, sales increased by 42.7% and market reach expanded by 213%. This program demonstrates the effectiveness of participatory and collaborative approaches in empowering women-led MSMEs sustainably